エイセイ オ リヨウ シタ キョクイキ デノ データ シュウロク g. ショウライ ケイカク ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 芳野, 赳夫; ヨシノ, タケオ; YOSHINO, Takeo (1980)
P(論文) 最近の実用人工衛星の発達は著しいものがあり,特に応用範囲と多用性の拡大は,目を見張るものがある.南極においても,従来のように超高層物理現象観測・気象観測以外に,1979年1月のNHKによるTV中継伝送のように新しく開拓すべき分野が非常に多くなってきた.本論文では,今後の南極における人工衛星利用について現在考慮し得る数例について説明し,特に近い将来無人観測点のデータ収集めため,自動データ収集装置を搭載する人工衛星の観測方法について詳述する. The objective of this paper is to show the main aspects of Japanese program to stablish an effective and reliable system to inter and intra-continents communication network for data and information transmission, to collect meteorological and geophysical data from Antarctica by the remote sensing system at present and in the near future. The difficulties to obtain environmental data from the, Antarctic territory are well known. The employment of earth orbiting satellites appears specially adequate to clarify several aspects related with this problem. The global system comprises geostationary and polar orbiting satellites to obtain qualitative and quantitative data, derived from imagery and automatic ground-based sensing stations (unmanned) called Data Collection Platforms (DCPs). departmental bulletin paper